Goniometer Crosstalk Compensation for Knee Joint Applications - Helenice Jane Cote Gil Coury; Gert-Åke Hansson; Tatiana de Oliveira Sato (Sensors, 2010)
Electrogoniometers are prone to crosstalk errors related to endblocks rotation (general crosstalk) and to the characteristics of each sensor (individual crosstalk). The aim of this study was to assess the crosstalk errors due to endblock misalignments and to propose a procedure to compensate for these errors in knee applications. A precision jig was used to simulate pure ±100° flexion/extension movements. A goniometer was mounted with various degrees of valgus/varus (±20°) and rotation (±30°) misalignments. For valgus/varus misalignments, although offset compensation eliminated the error in the valgus/varus recordings for 0° of flexion/extension and reduced it to a few degrees for small (±30°) flexion/extension angles (root mean square error = 1.1°), the individual crosstalk caused pronounced errors for large (±100°) angles (18.8°). Subsequent compensation for this crosstalk reduced these errors to 0.8° and 4.5°, respectively. For rotational misalignment, compensation for the general crosstalk by means of coordinate system rotation, in combination with compensation for the individual crosstalk, reduced the errors for small (±30°) and large (±100°) flexion/extension angles from 3.6° to 0.5° and from 15.5° to 2.4°, respectively. Crosstalk errors were efficiently compensated by the procedures applied, which might be useful in preprocessing of knee functional data, thereby substantially improving goniometer accuracy.